Grain alignment due to magnetic-field annealing in MnBi:Bi nanocomposites. (18th October 2016) - Zhang, W Y; Kharel, P; George, T; Li, X Z; Mukherjee, P; Valloppilly, S; Sellmyer, D J
Abstract: High-anisotropy arc-melted and field-annealed Mn100− x Bi x ( x = 50–65) alloys have been investigated. Samples predominantly consist of low-temperature phase (LTP) MnBi and elemental Bi, where the LTP volume fraction and sample magnetization decrease with increasing x . All samples are hard ferromagnetic at room temperature and demonstrate a structural and magnetic phase transition at 630 K. For Mn35 Bi65, the highest values for coercivity (4.6 kOe), magnetization remanence ratio (0.97), and energy product (4.9 MGOe) are measured at 540 K, near the melting point of bismuth. We explain the trend in magnetic properties as a consequence of c -axis alignment of MnBi grains facilitated by the molten Bi during magnetic field annealing.